Transforming teaching with emerging technologies: Implications for higher education institutions - Bozalek, Vivienne; Ng’ambi, Dick; Gachago, Daniela (South African Journal of Higher Education, 2016)
A gulf is widening between technologies used by students, those used by educators and those provided by institutions. However, knowledge about the impact of so-called emerging technologies on learning or the readiness of higher education institutions (HEIs) to engage with such technologies in the South African context is relatively thin. This paper uses Rogers’ (2003) diffusion of innovations model as a conceptual framework to examine the diffusion, adoption and appropriation of emerging technologies in South African HEIs. We report on a survey which examined how emerging technologies are used in innovative pedagogical practices to transform teaching and learning across South African HEIs. The paper concludes that, in order to foster a greater uptake or more institution-wide diffusion of use of emerging technologies, institutional opinion leaders need to purposefully create an enabling environment through giving recognition to and communicating with change agents, and developing policies that will encourage institutional-wide engagement with emerging technologies.